Differences in the Prices of Vulnerable Options with Different Counterparties. Issue 2 (19th May 2016) - Wang, Xingchun
Abstract: In this paper, a new pricing model is proposed to investigate the differences in the prices of vulnerable options with different counterparties. I start by specifying the dynamics of the market portfolio, and then break down the risk of the underlying asset and the assets of the counterparties into systematic and idiosyncratic risk, which allows me to distinguish the counterparties from these two kinds of risk. Finally, the derived pricing formulae are used to illustrate the differences between vulnerable option prices. © 2016 Wiley Periodicals, Inc. Jrl Fut Mark 37:148–163, 2017